Revealing sodium ion storage mechanism in hard carbon - Alvin, Stevanus; Yoon, Dohyeon; Chandra, Christian; Cahyadi, Handi Setiadi; Park, Jae-Ho; Chang, Wonyoung; Chung, Kyung Yoon; Kim, Jaehoon (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Although many studies have demonstrated the excellent potential of hard carbon as an anode in sodium ion batteries, the contribution of its active sites to the capacities of the sloping and plateau voltage regions is not yet clear. Herein, systematical investigation of the relationship between the active sites and sodium ion (Na+) storage in the sloping and plateau voltage regions was presented. In light of the physicochemical properties of the lignin-derived hard carbon (graphitization degree, interlayer spacing, micropore size distribution, and specific surface area), the results of Na+ ion diffusivity, and the change in these properties during Na+ ion insertion/extraction (as characterized by ex situ techniques), new mechanistic insights into Na+ ion storage were proposed. At the beginning of the sodiation process, Na+ ions were adsorbed on defect/edge sites; then partial micropore filling occurred in the sloping region above 0.1 V. In the plateau region below 0.1 V, Na+ ions were intercalated in the graphitic layers, and further adsorption in the micropores occurred near the cutoff potential. Furthermore, sodium clustering occurred below 0.1 V owing to the high concentration of Na+ ions in the micropores. (c) 2019 Elsevier Ltd. All rights reserved.
Keywords: ANODE MATERIALS; ELECTRODE MATERIALS; LITHIUM; LIGNIN; INTERCALATION; BATTERIES; METAL; OIL; LI; NA